Respuesta :
Answer:
x = 5.2
Step-by-step explanation:
[tex]f(x) = -5x + 11 + 3[/tex]
Let's first simplify our first function:
[tex]f(x) = -5x + 11 + 3\\f(x) = -5x + 14[/tex]
Now, we just need to set this function equal to our other given function.
[tex]f(x) = -5x+14\\f(x) = -12\\-5x + 14 = -12[/tex]
Now, we can add 12 to both sides:
[tex]-5x + 14 + 12 = -12 + 12\\-5x + 26 = 0[/tex]
Now, add 5x to both sides:
[tex]-5x+26 = 0\\26 = 5x\\[/tex]
Finally, we'll divide both sides by 5:
[tex]26/5 = 5x / 5\\5.2 = x\\x = 5.2[/tex]
Answer: x = 5.2